Unity, Complexity, dan Intensity Lukisan Karya Yazid - Yoan Fahira; Yandri Yandri; Maulid Hariri Gani (Institut Seni Indonesia Padang Panjang, 2021)
This study discusses how to understand the unity, complexity, and intensity of Yazid's painting using Monroe Beardsley's theory. Yazid is a West Sumatran artist who is quite famous for his naturalist flow and cannot be separated from the concept of natural beauty. This study uses a qualitative method which includes observation, interviews, and literature study. The research was conducted in the cities of Padang, Padang Pariaman and Padangpanjang, West Sumatra. After conducting research, it was found that Unity (unity) in Yazid's paintings as a whole shows how the arrangement of lines, colors, and compositions are produced in a perfect shape so that it looks like a unity. This makes for distinctive strokes and soft colors and object capture. The complexity of Yazid's paintings can be seen in the lighting which is described as similar to what is captured by the five senses so that the object does not look simple. How Yazid tries to present the refraction of light that is shown in each of his paintings. The intensity (seriousness) in Yazid's paintings can be seen in the lighting as the key in each of his works.